STUDY OF RECIRCULATING FLOW AROUND COASTAL STRUCTURE BY USING LABSWETM - Mohd Safri, Ahmad El Afify (Universiti Teknologi PETRONAS, 2017)
Breakwaters that are built at coastal area is a type of hard protection measure to protect the coastline, port, harbour or estuaries from the hydrodynamic effects due to severe waves condition. However, the presence of breakwaters will disrupt the natural condition of flow by dissipating, reflecting and refracting the incoming waves to produce calmer waves at the leeside of the structure. Thus, the flow separation occurs due to the blockade of breakwater which forming the recirculating flow inside the breakwater. This study is to simulate the recirculating flow around the breakwater at Chendering Fishery Port, Terengganu, Malaysia by using Lattice Boltzmann Method for shallow water equation with turbulence modelling (LABSWETM). The results of recirculating flow are analysed in the perspective of flow pattern and flow velocity.